The Herd Health Handbook for Goat Producers: Vaccination Protocol and Quality Assurance Measures for Goats: FAMU004/FAMU004, 9/2009 - Mobley, Ray; Lyttle-N’guessan, Carmen; Peterson, Thomas (EDIS, 2009)
FAMU004, a 9-page fact sheet by Ray Mobley, Carmen Lyttle-N'guessan, and Thomas Peterson, outlines a year-round preventive-based health maintenance program for goats, including schedules for vaccinations and anthelmintics, and common medications with approximate withdrawal times. Published by the Florida A & M University Extension, September 2009.